Quality and sustainability of tourism development in Copper Canyon, Mexico: Perceptions of community stakeholders and visitors - Gonzalez Herrera, Manuel Ramon (2018)
The assessment of tourism development, based on the perspectives and opinions obtained from hosts and visitors could be considered as a basic requirement for the participatory management of destination sustainability. The general objective of this research is to study the contrasted perceptions of tourism development in Copper Canyon Park, according to the opinions of hosts and visitors, with the purpose of evaluating the perceived quality and sustainability of the destination within the context of an implanted territorial tourism development model. In this study, a characterization of the tourism development of Copper Canyon Park was conducted, local public opinion relating to the implanted tourism development model was studied, and perceptions of visitors regarding the destination were analyzed. Utilizing this methodology allowed the identification of compatibilities and incompatibilities, relating to the convergence between the community's perceptions, the visitors' experiences, and the characteristics of the receiving environment.